2019
DOI: 10.1186/s12981-019-0221-7
|View full text |Cite
|
Sign up to set email alerts
|

HIV late presentation and advanced HIV disease among patients with newly diagnosed HIV/AIDS in Southwestern China: a large-scale cross-sectional study

Abstract: ObjectiveThis study aimed to investigate the prevalence of HIV late presentation and advanced HIV disease and to identify the factors associated with HIV late presentation and advanced HIV disease among patients with newly diagnosed HIV/AIDS in the Guangxi Zhuang Autonomous Region, in Southwestern China.MethodsPatients with newly diagnosed HIV registered in the HIV surveillance system of Guangxi Centers for Disease Control between January 2012 and December 2016 were included in this study.ResultsOf 45,118 newl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
56
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 45 publications
(41 reference statements)
11
56
2
Order By: Relevance
“…Previous studies have shown that patients with a late diagnosis of HIV infection had a higher risk of mortality than those with an early HIV diagnosis [34], and universal ART among late presentation patients reduced mortality by just 10% [35]. Late presentation is de ned well as, a patient diagnosed with the rst CD4 + cell count < 350/μL, or a patient with AIDS-de ning illness regardless of CD4 + cell count during diagnosis [8,[36][37]. In this study, the median CD4 + cell count in the ADE group was 29.00 cells/ μL (IQR: 12.00-116.50), and 96.05% of patients with ADE had late presentation, demonstrating that most of patients with ADE were in an advanced stage of HIV/AIDS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that patients with a late diagnosis of HIV infection had a higher risk of mortality than those with an early HIV diagnosis [34], and universal ART among late presentation patients reduced mortality by just 10% [35]. Late presentation is de ned well as, a patient diagnosed with the rst CD4 + cell count < 350/μL, or a patient with AIDS-de ning illness regardless of CD4 + cell count during diagnosis [8,[36][37]. In this study, the median CD4 + cell count in the ADE group was 29.00 cells/ μL (IQR: 12.00-116.50), and 96.05% of patients with ADE had late presentation, demonstrating that most of patients with ADE were in an advanced stage of HIV/AIDS.…”
Section: Discussionmentioning
confidence: 99%
“…The "Treat for All" policy was implemented in 2016, and HIV positive individuals would be treated after diagnosis of HIV regardless of their CD4 + cell count [5][6][7]. However, research showed that 45.1% patients in the advanced stages of AIDS when they were diagnosed [8], which might be the main reason for the high mortality rate in HIV positive individuals, even when they are on ART.…”
Section: Introductionmentioning
confidence: 99%
“…However, throughout the period of increasing implementation of ART, China's National Free Antiretroviral Treatment Program (NFATP) has been largely successful, with an overall reduction in virological failure and HIV drug resistance since 2008 [9]. Although there is limited access to many antiretrovirals (ARVs) in China, data from the NFATP study prove that understanding the scientific basis and clinical implications of HIVDR is useful in order to shape appropriate surveillance, inform treatment algorithms, and manage difficult cases [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The "Treat for All" policy was implemented in 2016, and HIV positive individuals would be treated after diagnosis of HIV regardless of their CD4 + cell count [5][6][7] . However, research showed that 45.1% patients were in the advanced stages of AIDS when they were diagnosed [8] , which might be the main reason for the high mortality rate in HIV positive individuals, even when they are on ART.…”
Section: Introductionmentioning
confidence: 99%
“…Late diagnosis and delayed treatment of HIV infection contribute to the development of opportunistic infections, such as pneumocystis pneumonia, Talaromyces marneffei infection, etc. In Guangxi, a recent retrospective study revealed that 70.2% of newly diagnosed HIV cases from 2012 to 2016 had a late presentation, and 45.1% had advanced HIV disease [8] . Most of patients with late presentation, advanced HIV disease, or ADE have relatively low CD4 + cell counts or develop AIDS symptoms.…”
Section: Introductionmentioning
confidence: 99%